ALLOKRANOIPLASTY WITH 3D IMPLANTS FOR SKULL DEFECT (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Currently, the introduction of the principles of minimally invasive microneurosurgery, the use of modern neuroimaging methods, and comprehensive adequate neuroreanimation intensive care have reduced mortality in severe traumatic brain injuries and brain tumors, but do not reduce the number of patients with post-trepanation skull defects [1,8]. Despite the long history of study, at the moment the problem of choosing a method for restoring the integrity of the skull after resection trepanations, removal of space-occupying lesions affecting the bones of the vault and base of the skull is still relevant [2]. Violation of the tightness of the skull leads to the formation of a new pathological condition - "trepanned skull syndrome". The inability of the post-trepanation defect to spontaneously restore bone tissue, functional and organic disorders that occur in patients serve as reasons for cranioplasty [2,3].